2008
DOI: 10.1115/1.2898876
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Spur Gear Efficiency

Abstract: In this study, a test methodology was developed for the measurement of spur gear efficiency under high-speed and variable torque conditions. A power-circulating test machine was designed to operate at speeds to 10,000rpm and transmitted power levels to 700kW. A precision torque measurement system was implemented, and its accuracy and repeatability in measuring torque loss in the power loop was demonstrated. Tests were conducted on gears with two values of modules and two surface roughness levels, operating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(74 citation statements)
references
References 23 publications
1
71
0
2
Order By: Relevance
“…It is common to that run-in takes place at some fraction of the target load (20% to 80%) and time (75,000 to 600,000 cycles). Much of the gear efficiency research performed still has not fully characterized the details of run-in and only utilize it as a starting procedure for tribotests [6,8,9]. Additionally, there is a gap in understanding all of the changes which occur during the initial phases of run-in which was identified by Blau [15].…”
Section: Chapter 1 Introduction Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common to that run-in takes place at some fraction of the target load (20% to 80%) and time (75,000 to 600,000 cycles). Much of the gear efficiency research performed still has not fully characterized the details of run-in and only utilize it as a starting procedure for tribotests [6,8,9]. Additionally, there is a gap in understanding all of the changes which occur during the initial phases of run-in which was identified by Blau [15].…”
Section: Chapter 1 Introduction Background and Motivationmentioning
confidence: 99%
“…Many techniques are utilized to decrease surface roughness and asperity contact, and thus, increase efficiency. Xiao et al and Petry-Johnson et al showed a reduction in gear tooth surface roughness was significant in reducing the mechanical losses for high speed and torque conditions [5,6].…”
Section: Chapter 1 Introduction Background and Motivationmentioning
confidence: 99%
“…They indicated that the churning losses mainly consists of four parts: 1) Power losses are generated by the lubricating oil which is in accelerating gear; 2) Power losses are generated by lubricating oil which move in the meshing gear cavity; 3) Power losses are generated by lubricating oil splash in the pool; 4) When the lubricating oil come into meshing gear position, power losses are generated by bending lubricating oil. Changenet et al [8,9] pointed out that most of the current gear churning losses formulas can be more precise calculate the churning losses that were generated in meshing gear or single disk, Petry-Johnson et al [10] obtained same calculation results by analysing the experimental data which is measured under different conditions. Kahraman et al [5] claim that the churning losses is mainly divided into two parts: 1) When the gear is rotated, the power losses were caused by the movement of the lubricating oil stuck on the gear (This part includes three aspects: power losses were generated by interaction of the periphery of gear and lubricating oil; power losses were generated by interaction of the face of gear and lubricating oil; Scroll power losses were generated by lubricating oil in gear cavity); 2) When the gear is meshed, the gap between the two gears is changed and makes the oil being sucked and extruded which cause power losses.…”
Section: Introductionmentioning
confidence: 54%
“…Several experimental studies have been published related to gear mesh efficiency. Petry-Johnson et al [2], Naruse et al [3,4] and Maghales [5] showed that reducing the module can have a significant influence on gear mesh losses because of the reduced sliding friction. Martins et al [6] measured the average friction coefficient of dip-lubricated FZG gears and reported that the friction coefficient decreases with increasing rotational speed and increases with transmitted torque.…”
Section: Introductionmentioning
confidence: 99%
“…Power loss in gearboxes is usually divided into load-dependent and load-independent power losses [1,2]. The load-independent losses are related to moving parts immersed in the lubricant, while the load-dependent losses result from contacting bodies moving relative to each other.…”
Section: Introductionmentioning
confidence: 99%